2019
DOI: 10.1177/2032284419861816
|View full text |Cite
|
Sign up to set email alerts
|

Prison and the brain: Neuropsychological research in the light of the European Convention on Human Rights

Abstract: Prison is by its nature a deliberately impoverished environment, with few physical, mental and social activities. Various studies have shown negative effects of an impoverished environment on animal as well as human brain functions. A recent study in a Dutch remand prison showed that brain functions connected with self-regulation decline after 3 months of imprisonment. Reduced self-regulation appears to be a risk factor for recidivism. In this article, we examine the legal implications of these neuropsychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…5 That is, punishment for the sake of punishment, solely by reference to one's past criminal offense. 6 (Ligthart et al 2019a;Meijer 2017). This obligation is one of means, not of result.…”
Section: Human Rights: the Obligation To Facilitate Resocializationmentioning
confidence: 99%
See 1 more Smart Citation
“…5 That is, punishment for the sake of punishment, solely by reference to one's past criminal offense. 6 (Ligthart et al 2019a;Meijer 2017). This obligation is one of means, not of result.…”
Section: Human Rights: the Obligation To Facilitate Resocializationmentioning
confidence: 99%
“…One should bear in mind that prison is a deliberately impoverished environment. Regardless of the imposed regime or security level, it entails physical, mental, and social inactiveness of detainees (Ligthart et al 2019a). Various studies have depicted the negative effects that an impoverished environment has on human brain functions and human flourishing.…”
Section: Human Rights: the Obligation To Facilitate Resocializationmentioning
confidence: 99%
“…this study with prisoners lacks that analysis. As prisoners show a tendency towards cognitive vulnerabilities (Ligthart et al, 2019;Meijers et al, 2018;Ogilvie et al, 2011), more studies are needed that focus on validating psychological assessment instruments for prison settings and exploring the benefits of restorative justice approaches.…”
Section: F I G U R Ementioning
confidence: 99%
“…According to research from the World Health Organization, within prisons the prevalence of mental disorders is significantly higher than in the general population (Durcan and Zwemstra, 2014) and it has also been suggested that there are ten times more individuals with a mental disorder in jail than in mental hospitals in the United States (Torrey et al, 2014;Semenza & Grosholz, 2019). Instead of fulfilling a positive function, the prison impoverished environments could end up violating minimum human rights standards (Ligthart et al, 2019), and even become criminogenic factors (Vieraitis et al, 2007;Cid, 2009;Cullen et al, 2011;Meijers et al, 2018;Wallace and Wang, 2020).…”
Section: Adverse Neuropsychological Effects Of Imprisonmentmentioning
confidence: 99%